Exploring Effective Approach to Teaching Thermal Physics: Comparing 5E Model, Differentiated Instruction and Conventional Teaching - Kenneth Darko Ateko; Isaac Owusu-Mensah; George Oduro-Okyireh (Scientia Publica Media, 2025)
In this study, the effects of 5E Instructional Model (5E), Differentiated Instruction (DI) and conventional teaching method on Senior High School (SHS) physics students’ academic performance in Thermal Physics were compared. Method: By employing a quasi-experimental pretest/posttest non-equivalent control group design, 291 SHS 2 physics students were used from six intact classes which were randomly selected from three SHSs in the Mampong Municipality and Sekyere South District. The hypotheses were tested using one-way ANCOVA and two-way ANCOVA at α=0.05. The results showed that there was a significant effect of at least one of the teaching methods on the academic performance of students (F(1,287)=150.766, p=0.001<0.05), with students taught using DI obtaining the highest adjusted mean scores of 18.978 (std. error = 0.437), followed by those taught using 5E group (adjusted mean = 16.373, std. error=0.430), and those taught using the conventional teaching method (adjusted mean score = 13.734, std. error = 0.452). Also, there was a significant interaction between gender and teaching method (F(1,284)=241.395, p=0.001<0.05) with no significant difference observed between male and female students taught using DI (mean difference=0.233, p=0.765) and 5E (mean difference=0.75, p=0.532), but a significant difference in academic performance between male and female SHS students taught using conventional teaching method (mean difference=8.284, p=0.000). It was therefore recommended, amongst others, that SHS physics teachers in Mampong Municipality and Sekyere South District should consider differentiating their students in order to tailor Thermal Physics lessons to all students, which will help them perform better.